Assessment of Peri-Implant Bone Loss in Smokers vs. Non-Smokers: A Prospective Study - Sumit Bhatt; TS Reshma; Jerry Mammen; Deepak Sharma; Varun Raj; Sameer Gupta (Journal of Pharmacy and Bioallied Sciences)
Background: One important aspect affecting dental implants’ long-term success is peri-implant bone loss. Because smoking has a negative impact on osseointegration and healing, it has been recognized as a risk factor that might hasten peri-implant bone resorption. Materials and Methods: One hundred patients in need of single dental implants were recruited, fifty of whom were smokers and fifty of whom were not. Titanium implants with identical surface properties were given to each patient. Standardized periapical radiographs were used to quantify marginal bone loss at baseline (implant implantation), six months, and twelve months. Clinical data were also documented, such as bleeding on probing (BOP) and peri-implant probing depth (PPD). ANOVA and paired t-tests were used in the statistical study to compare the groups’ bone loss. Results: The average peri-implant bone loss at 6 months was 0.6 ± 0.3 mm for non-smokers and 1.2 ± 0.4 mm for smokers (P < 0.05). At 12 months, smokers saw a 2.1 ± 0.5 mm increase in bone loss, whereas non-smokers experienced a 1.0 ± 0.4 mm increase (P < 0.05). Smokers had a substantially greater peri-implant probing depth (3.8 ± 0.6 mm) than non-smokers (2.5 ± 0.5 mm, P < 0.05). Additionally, smokers had 70% more bleeding on probing than non-smokers (40%). Conclusion: According to the research, smoking has a detrimental effect on peri-implant health and considerably speeds up peri-implant bone loss. Compared to non-smokers, smokers showed higher levels of inflammation, increased probing depth, and marginal bone loss.